2018
DOI: 10.3389/fpsyt.2018.00341
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Activity of Prefrontal-Striatal Circuits in Internet Gaming Disorder: Changes With Cognitive Behavior Therapy and Predictors of Treatment Response

Abstract: Cognitive behavior therapy (CBT) is effective for the treatment of Internet gaming disorder (IGD). However, the mechanisms by which CBT improves IGD-related clinical symptoms remain unknown. This study aimed to discover the therapeutic mechanism of CBT in IGD subjects using resting-state functional magnetic resonance imaging (rsfMRI). Twenty-six IGD subjects and 30 matched healthy controls (HCs) received rsfMRI scan and clinical assessments; 20 IGD subjects completed CBT and then were scanned again. The amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 46 publications
2
55
0
Order By: Relevance
“…Overall, the interventions had a positive effect on IGD symptoms (D. H. X. Han et al, 2018;Kang et al, 2018;W.…”
Section: Gaming Addiction Interventionsmentioning
confidence: 99%
“…Overall, the interventions had a positive effect on IGD symptoms (D. H. X. Han et al, 2018;Kang et al, 2018;W.…”
Section: Gaming Addiction Interventionsmentioning
confidence: 99%
“…Resting-state functional magnetic resonance imaging (rsfMRI) has also shown that CBT is effective. One study of 26 IGD subjects who received rsfMRI scans and clinical assessments after undergoing CBT showed that the time spent gaming weekly was significantly shorter, concluding that CBT could regulate the abnormal low-frequency fluctuations in prefrontal-striatal regions in IGD subjects and could improve IGD-related symptoms 69…”
Section: Assessment and Treatmentmentioning
confidence: 99%
“…Abnormal (i.e., differing from healthy comparison subjects) executive control and reward processing have been reported in IGD using resting-state fMRI FC, which detects synchronized spontaneous activity among anatomically distinct regions or networks. For example, studies have reported decreased FC among executive-control and reward-related brain regions (Chen et al, 2016;Han et al, 2018;Kim et al, 2019;Yuan et al, 2017), suggesting imbalanced networks relating to executive control and reward processes. Theoretical models of IGD have proposed that executive control and reward circuits contribute importantly and that the trade-off between these circuits may promote poorly controlled behaviors in IGD and other addictive disorders (Brand et al, 2019;Dong & Potenza, 2014).…”
Section: Introductionmentioning
confidence: 99%